Impact of E-Pedagogy in English E-Class in Higher Education of Nepal - Khadka, Bishnu Kumar (Bodhi: An Interdisciplinary Journal, 2023)
Though the use of e-pedagogy in education has been advocated, it had not been well-practiced before the COVID-19 pandemic period in Nepalese education context. In this connection, thisstudy aimsto reflect the context and explore the use and impact of e-pedagogy in terms of access and quality with the practices of it by the university English teachers and students of Nepal during pandemic and post pandemic contexts. The mixed-method research design was used collecting data from an online survey questionnaire and internet based semi-structured interviews among the participants from the teachers (N=20) and students (N=80) of five universities for quantitative data and for qualitative data from two students and two teachers of two the universities of Nepal. The findings of the study revealed that on average, 23.6% of university teachers and students have a positive impact of e-pedagogy where KU followed by MU, TU, PU and FWU teachers and students were found to be using more often it in terms of joining e-class and using resources (30%), interaction (33%), regularity (31%), techno-based learning (average 21.2%:MU–28%), searching internet-based resources (TU–28%), attending online examinations (average 17.4%:KU21%), participating online training/workshop/ conference (average 23.8%:KU–26%), and learner autonomy (average 15.4%:PU-19%) supported by the qualitative data. Furthermore, the use of e-pedagogy in ELT was found to be no longer being used regularly pandemic period onwards and suggested to be practiced as the regular part of teaching and learning in a blended way. Overall, e-pedagogy has had a positive impact on teaching-learning in English e-class during the pandemic period.